4
$\begingroup$

Consider the following integral. Given fixed $x,y>0$, $$I(x,y):=\int_0^1\frac{x}{\sqrt{2\pi t^3}}\exp\left(-\frac{x^2}{2t}\right)\cdot\frac{1}{\sqrt{2\pi(1-t)}}\exp\left(-\frac{y^2}{2(1-t)}\right)~\mathrm dt.$$

I have reason to believe that $$I(x,y)=\frac{1}{\sqrt{2\pi}}\exp\left(-\frac{(x+y)^2}{2}\right),$$ but can't prove this.


The closest I got to a solution (though it's not much) is this: If $(W_t)_{t\geq0}$ is a standard Brownian motion and $$H_x:=\inf\{t\geq0:W_t=x\}$$ is the first hitting time of some point $x>0$, then, $$\mathbb P\{H_x=\mathrm dt\}=\frac{x}{\sqrt{2\pi t^3}}\exp\left(-\frac{x^2}{2t}\right).$$

By the strong Markov property, if $H_x$ and $H_y$ are independent Brownian hitting times, then $$H_x+H_y=_dH_{x+y},$$ where the above is an equality in distribution. Thus, it follows from a convolution argument that if $$I'(x,y):=\int_0^1\frac{x}{\sqrt{2\pi t^3}}\exp\left(-\frac{x^2}{2t}\right)\cdot\frac{y}{\sqrt{2\pi (1-t)^3}}\exp\left(-\frac{y^2}{2(1-t)}\right)~\mathrm dt,$$ then $$I'(x,y)=\mathbb P\{H_{x+y}=\mathrm d1\}=\frac{x+y}{\sqrt{2\pi}}\exp\left(-\frac{(x+y)^2}{2}\right).$$

So the integral $I(x,y)$ is somewhat similar, but instead of being a convolution of two hitting time densities, it is the convolution of one hitting time density together with a Gaussian density where the variance is integrated.

$\endgroup$
  • 3
    $\begingroup$ The lack of symmetry in $x$ and $y$ would seem to make a result that's symmetric in $x$ and $y$ unlikely. $\endgroup$ – StephenG Aug 2 '17 at 0:55
  • $\begingroup$ Looks like there is symmetry... $\int_{a}^{b} f(t) dt = \int_{a}^{b} f(a+b-t) dt$, so if, $F(x,y) = \frac{\partial{I(x,y)}}{\partial y}$, then $F(x,y) = F(y,x)$ $\endgroup$ – Aryabhata Aug 2 '17 at 2:25
0
$\begingroup$

Using Aryabhata's comment as an inspiration, we see that, using my question's notation, $$\frac{\partial I(x,y)}{\partial y}=-I'(x,y)=-\frac{(x+y)}{\sqrt{2\pi}}\exp\left(-\frac{(x+y)^2}{2}\right).$$

Therefore, there is some function $f$ of $x$ such that $$I(x,y)=\int -I'(x,y)~\mathrm dy=\frac{1}{\sqrt{2\pi}}\exp\left(-\frac{(x+y)^2}{2}\right)+f(x).$$

In order to show that $f(x)=0$, we need only prove that $$I(x,0)=\int_0^1\frac{x}{\sqrt{2\pi t^3}}\exp\left(-\frac{x^2}{2t}\right)\cdot\frac{1}{\sqrt{2\pi(1-t)}}~\mathrm dt=\frac{1}{\sqrt{2\pi}}\exp\left(-\frac{x^2}{2}\right).$$

To see this, note that the indefinite integral (Mathematica) is given by $$\int\frac{x}{\sqrt{2\pi t^3}}\exp\left(-\frac{x^2}{2t}\right)\cdot\frac{1}{\sqrt{2\pi(1-t)}}~\mathrm dt=-\frac{e^{-\frac{x^2}{2}} \text{erf}\left(\frac{x}{\sqrt{2} \sqrt{\frac{1}{1-t}-1}}\right)}{\sqrt{2 \pi }},$$ where $$\mathrm{erf}(z):=\frac{2}{\sqrt{\pi}}\int_0^ze^{-x^2}~\mathrm dx$$ is the error function. At this point, we simply use the fundamental theorem of calculus.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.